2018
DOI: 10.5194/amt-11-81-2018
|View full text |Cite
|
Sign up to set email alerts
|

Precipitable water vapour content from ESR/SKYNET sun–sky radiometers: validation against GNSS/GPS and AERONET over three different sites in Europe

Abstract: Abstract. The estimation of the precipitable water vapour content (W ) with high temporal and spatial resolution is of great interest to both meteorological and climatological studies. Several methodologies based on remote sensing techniques have been recently developed in order to obtain accurate and frequent measurements of this atmospheric parameter. Among them, the relative low cost and easy deployment of sun-sky radiometers, or sun photometers, operating in several international networks, allowed the deve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 32 publications
7
32
0
1
Order By: Relevance
“…Indeed, an SH increase occurs on the first day of the sequence (starting from minimum values of ∼8 g kg −1 in the morning to about 11 g kg −1 in the evening) as soon as the wind starts blowing and high values (> 13 g kg −1 ) endure for the rest of the week, likely indicating that the dry air, typical of the more mixed mountain PBL (Henne et al, 2005;Mélin and Zibordi, 2005), is replaced by more stagnating, and humidified, air masses characteristic of hot summer days in the Po Valley (Bucci et al, 2018). This scenario is compatible with recent findings by Campanelli et al (2018), who performed water vapour measurements with the POM-02 at Aosta-Saint Christophe and found that moist air masses are mainly coming from the east.…”
Section: Meteorological Variables and Back-trajectoriessupporting
confidence: 90%
“…Indeed, an SH increase occurs on the first day of the sequence (starting from minimum values of ∼8 g kg −1 in the morning to about 11 g kg −1 in the evening) as soon as the wind starts blowing and high values (> 13 g kg −1 ) endure for the rest of the week, likely indicating that the dry air, typical of the more mixed mountain PBL (Henne et al, 2005;Mélin and Zibordi, 2005), is replaced by more stagnating, and humidified, air masses characteristic of hot summer days in the Po Valley (Bucci et al, 2018). This scenario is compatible with recent findings by Campanelli et al (2018), who performed water vapour measurements with the POM-02 at Aosta-Saint Christophe and found that moist air masses are mainly coming from the east.…”
Section: Meteorological Variables and Back-trajectoriessupporting
confidence: 90%
“…This kind of secondary inorganic aerosol was indeed found in high concentrations in the Po basin by previous studies (e.g. Putaud et al, 2002Putaud et al, , 2010Carbone et al, 2010;Larsen et al, 2012;Saarikoski et al, 2012;Gilardoni et al, 2014;Curci et al, 2015). Here we further tested on a longer dataset whether the sum of the nitrate-and sulfate-rich factors (i.e.…”
Section: Chemical Species Within the Advected Aerosol Layerssupporting
confidence: 79%
“…The slope of curvature (M) represents the average characterization of the solar aureole shape across the scattering angle 3.2-6.0 • range in which a large magnitude signifies the potential presence of large particles as curvature increases with increasing scattering angle across the forward scattering peak. The Micro-Pulse Lidar Network (MPLNET) is a global network of lidars monitoring the vertical distribution of aerosols and clouds (Welton et al, 2000;Welton and Campbell, 2002;Campbell et al, 2002). To determine the thresholds for these Sun photometer solar aureole curvature parameters for different surface types and aerosol environments, the MPLNET lidar cloud identification database was used at eight collocated AERONET sites as shown in Table 3.…”
Section: Novel Cirrus Removal Methods Utilizing Solar Aureole Curvaturementioning
confidence: 99%